Production of biohydrogen by fermentation of organic waste as the basis of alternative energy in Ukraine - Tashyriev, O.B.; Hovorukha, V.M.; Havryliuk, O.A.; Yastremska, L.S. (Problems of Environmental Biotechnology, 2023)
On the basis of thermodynamic forecast, a biotechnological approach was developed and experimentally confirmed for fast and effective disposal of multicomponent organic waste with the production of environmentally clean energy carrier H2 and a number of valuable products.